Enhancing Problem-Solving Skills through the Student Facilitator and Explaining Model: An Exploratory Study - Aulina, Choirun Nisak; Rocmah, Luluk Iffatur; Shofiyah, Noly; Ratih, Elin Salina (Jurnal Pendidikan Progresif, 2025)
Enhancing Problem-Solving Skills through the Student Facilitator and Explaining Model: An Exploratory Study. Objectives: This study investigates the potential of the Student Facilitator and Explaining (SFE) model to improve undergraduate students’ problem-solving skills during microteaching practice. Methods: A quantitative, single-group pretest-posttest design was employed, involving 21 students enrolled in the Microteaching course of the Early Childhood Education (PG PAUD) program. The instrument consisted of six dimensions: persistence, divergent thinking, convergent thinking, motivation, environment, and general knowledge and skills, measured using a five-point Likert scale. Pretest and posttest data were analyzed using paired sample t tests to determine statistical significance. Findings: Results showed significant improvements across all dimensions of problem-solving skills. The most substantial gains were observed in divergent thinking (Mdiff = 18.57, t = 13.54, p < 0.001), general knowledge and skills (Mdiff = 18.05, t = 13.90, p < 0.001), and motivation (Mdiff = 17.81, t = 14.12, p < 0.001). All dimensions demonstrated statistically significant enhancement (p < 0.001), indicating that the SFE model effectively fosters students’ cognitive flexibility, persistence, and self-motivation in addressing instructional problems. Conclusion: The SFE model enhances students’ problem-solving abilities by promoting active engagement, collaborative reasoning, and reflective learning within Microteaching courses. These findings highlight the potential of student-centered instructional models to develop both cognitive and professional competencies in teacher education. Future research using control groups and larger samples is recommended to strengthen the validity and generalizability of these results. Keywords: problem-solving skills, SFE model, microteaching, pedagogical strategy.